2021
DOI: 10.1002/asna.202113922
|View full text |Cite
|
Sign up to set email alerts
|

Neutron stars origins and masses

Abstract: We present in this talk an overview of the neutron star origin events and masses. Using the existing sample of ∼80 measured neutron star masses, we show that the distribution requires more than one mass-scale and that its highest value inferred from the sample is compatible with 2.5M ⊙ , suggesting that very heavy neutron stars may be present in Nature. The case of some "spider" systems and the enigmatic high-mass object in the GW190408 event, as well as the highest measured values from other binaries may supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These observations have challenged our view about the mass of neutron stars, which peaks at about the Chandrasekhar limit of 1.43.33333ptM$1.4\hspace*{3.33333pt}{M}_{\odot}$. [ 91 ] A recent determination of the mass of the pulsar PSR J0952‐0607, the fastest known rotating neutron star in the disk of the Milky Way, yielded a maximum mass of the order of 2.523.33333ptM$2.52\hspace*{3.33333pt}{M}_{\odot}$ [M =(2.35±0.17)3.33333ptM$=(2.35\pm 0.17)\hspace*{3.33333pt}{M}_{\odot}$]. The mass of PSR J0952‐0607 challenges our understanding of the equation of state for the dense matter.…”
Section: Discussionmentioning
confidence: 99%
“…These observations have challenged our view about the mass of neutron stars, which peaks at about the Chandrasekhar limit of 1.43.33333ptM$1.4\hspace*{3.33333pt}{M}_{\odot}$. [ 91 ] A recent determination of the mass of the pulsar PSR J0952‐0607, the fastest known rotating neutron star in the disk of the Milky Way, yielded a maximum mass of the order of 2.523.33333ptM$2.52\hspace*{3.33333pt}{M}_{\odot}$ [M =(2.35±0.17)3.33333ptM$=(2.35\pm 0.17)\hspace*{3.33333pt}{M}_{\odot}$]. The mass of PSR J0952‐0607 challenges our understanding of the equation of state for the dense matter.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of accurate observations on the masses and radii obtained from massive pulsars, the gravitational wave event GW170817, or PSR J0030+0451 massradius relation from Neutron Star Interior Composition Explorer (NICER) data have dramatically changed our understanding of the mass distribution of neutron stars, by challenging the paradigm according to which the mass of the neutron stars peaks at around the Chandrasekhar limit of 1.4M ⊙ [99]. For example, the mass of the pulsar PSR J0952-0607, the fastest known rotating neutron star in the disk of the Milky Way, has been determined recently, giving a maximal mass of the order of 2.52M ⊙ (M = 2.35 ± 0.17M ⊙ ).…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…However, the standard view on the neutron star masses has changed drastically recently, once more and more exact determinations of the neutron star masses became available [14]. A large number of accurate astronomical observations, as well as the detection of the gravitational waves, has clearly indicated that the masses of neutron stars vary in a much larger range than expected from the simple application of the Chandrasekhar limit.…”
mentioning
confidence: 99%
“…Still, in this bound the effects of the rotation and of the existence of ex-otic states of matter are ignored. On the other hand, a number of theoretical arguments, that seemed to be supported by the observational evidence, suggested that neutron stars had a characteristic, unique mass of the order of 1.4M ⊙ [2]. Assuming an interaction among neutrons, the role of the repulsive interactions should be important, thus leading to a numerical coincidence with the Chandrasekhar mass [3].…”
mentioning
confidence: 98%
“…Assuming an interaction among neutrons, the role of the repulsive interactions should be important, thus leading to a numerical coincidence with the Chandrasekhar mass [3]. This coincidence led to postulate that some specific physical processes at the birth of neutron star would uniquely fix its mass [2]. However, with the increase in the precision of the astronomical observations, the paradigm of a unique mass distribution around 1.4M ⊙ of the neutron stars has to abandoned, and the existence of neutron stars with light (1.174 ± 0.004M ⊙ ) [4], or heavy (2.140.010.09M ⊙ ) [5] masses is presently well established.…”
mentioning
confidence: 99%